Neo-adjuvant Chemotherapy in Malignant Ovarian Germ Cell Tumor - Maharjan, Pabitra; Lama, Poonam; Shrestha, Anisha; Karki, Onika; Sapkota, Simit; Pandit, Subhas; Shrestha, Suresh; Neupane, Sameer; Koirala, Srijana; Parajuli, Bandana; et al. (Nepalese Journal of Cancer, 2026)
Introduction: Malignant ovarian germ cell tumors (MOGCT) are common in young females, management of which is associated with fertility and reproductive concerns. Being highly chemo-sensitive, neo-adjuvant chemotherapy (NACT) prior to definitive surgery could help reduce disease burden and increase the possibility of organ preservation. Methods: A descriptive study was done on ovarian cancer patients with fertility concerns attending Civil Service Hospital of Nepal from 2015 to 2021. Clinical data were collected from hospital registry and telephonic inquiries followed by in-person interviews in all the participants regarding their treatment, present status, oncologic and fertility outcome. Results: Eighteen MOGCT fertility needs were identified, among which seven underwent NACT (39%) with fertility preserving surgery and were enrolled in the study. Mean age was 16.8 years (range: 15-19 years). Histologically, of total seven cases, three (43%) were Dysgerminoma in stage IC, three (43%) were yolk sac tumor (2 in stage IC and 1 in stage IIIC), and one (14%) were of mixed germ cell tumor at stage IIIC. All 7 patients underwent fertility preserving surgery after NACT. At the time of presentation, three were married and four were unmarried. Two (28%) patients had recurrence as they defaulted during treatment among which one patient died and the other came after 1 year and completed chemotherapy. Thus 85% (six in seven) of the cases are in complete remission, among which three conceived and had successful delivery. Conclusion: The present study supports NACT to be beneficial in offering fertility sparing surgery even in advanced stage MOGCT.